Composition of Environmental Parameters in Aquatic Sediments in West Sumatra - Suci Handayani; Zulkarnaini Zulkarnaini; Puti Sri Komala (Postgraduate, University of Mataram, 2024)
This study aims to identify the factors influencing environmental parameters in water and sediment and evaluate their impacts on ecosystems and biota, thereby providing a scientific basis for effective and sustainable water resource management. Measurements were conducted at 10 natural ecosystem locations comprising rivers, beaches, estuaries, and lakes in West Sumatra. The parameters measured in the water were temperature, pH, DO, and salinity, while in the sediment, pH, TOC, ammonium, nitrate, nitrite, phosphate, and sulfate were measured. The results of the environmental parameter analysis in the water were Temperature (26.3 ± 0.65°C), pH (7.62 ± 0.43), DO (4.5 ± 0.81 mg/L), and Salinity (13.78 ± 13.95 ppt). In the sediment, the results were pH (6.74 ± 0.86), TOC (1.49 ± 0.29%), Ammonium (12.95 ± 5.34 mg/L), Nitrite (76.33 ± 34.26 mg/L), Nitrate (31.60 ± 5.25 mg/L), Phosphate (29.5 ± 20.37 mg/L), and Sulfate (29.46 ± 8.23 mg/L). Overall, the factors affecting water and sediment parameters are biological activity, land input, and anthropogenic contaminants. The ability of sediment to accumulate and absorb particles and chemicals is one of the factors causing the high concentration of environmental parameters in sediment